Ribes fasciculatum Ameliorates High-Fat-Diet-Induced Obesity by Elevating Peripheral Thermogenic Signaling - Yuna Lee; Park, Yeo Jin; Lee, Bonggi; Park, Eunkuk; Kim, Hail; Choi, Chun Whan; KIM, MIN SOO (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Ribes fasciculatum has been consumed as a food and as a traditional medicine for treating autoimmune diseases and aging in diverse countries. A previous study showed that a mixture of Ribes fasciculatum and Cornus officinalis prohibited adipocyte differentiation and lipid accumulation in preadipocytes and suppressed diet-induced obesity. Nevertheless, the mechanism of R. fasciculatum to regulate energy homeostasis solely through thermogenic signaling remains unclear. Thus, we investigated its effects on energy homeostasis using R. fasciculatum fed to C57BL/6 mice with a 45% high-fat diet. Chronic consumption of R. fasciculatum decreased the body weight of obese mice with increasing food intakes and improved metabolic-syndrome-related phenotypes. Therefore, we further tested its thermogenic effects. Cold chamber experiments and qPCR studies indicated that R. fasciculatum elevated thermogenic signaling pathways, demonstrated by increased body temperature and uncoupling protein 1 (UCP1) signaling in the white and brown adipose tissues. Afzelin is one major known compound derived from R. fasciculatum. Hence, the isolated compound afzelin was treated with preadipocytes and brown adipocytes for cell viability and luciferase assay, respectively, to further examine its thermogenic effect. The studies showed that the response of afzelin was responsible for cell viability and the increased UCP1. In conclusion, our data indicated that R. fasciculatum elevated peripheral thermogenic signaling through increased UCP1 via afzelin activation and ameliorated diet-induced obesity.